Agama pada Masa Dewasa - Ayilzi Putri; Bitri Hariani Lubis; Aslamiyah Abda Daulay; Ramadan Lubis; Alde Rizky Pratama Siregar; Muhammad Fachrezy Risdi; Muhammad Nuha Hidayat (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This article aims to understand the role of religion in adulthood and how religious beliefs evolve with age. This research employs a literature review methodology by examining various sources related to the psychology of religion in adult individuals. The findings show that religion plays a significant role in providing emotional support, enhancing psychological well-being, and shaping life perspectives. Furthermore, religious commitment tends to increase with age, associated with the pursuit of meaning and life purpose. These findings suggest that religion can be a substantial source of mental strength for adults.